State of the‐Art for Extrudate Swell of Molten Polymers: From Fundamental Understanding at Molecular Scale toward Optimal Die Design at Final Product Scale. Issue 11 (16th November 2020) - Tang, Dahang; Marchesini, Flavio H.; Cardon, Ludwig; D'hooge, Dagmar R.
Abstract : Front Cover : In article number 2000340, Dagmar R. D'hooge and co‐workers highlight both the experimental and theoretical capabilities to control extrudate die swell for polymer material production by extrusion, which is a leading technology in the materials engineering field. Swelling takes place as polymer molecules are viscoelastic, implying that when they exit the extrusion equipment they recoil changing the dimensions and thus the product stability.